OXYGEN ISOTOPE EXCHANGE PROCESSES AND DISEQUILIBRIUM BETWEEN CALCITE AND FORSTERITE IN AN EXPERIMENTAL C-O-H FLUID - AN EXPERIMENTAL STUDY - Zheng Y.F.; Satir M.; Metz P.; Sharp Z.D. (My University, 1999)
Oxygen isotope exchange between calcite and forsterite were investigated in the presence of a large amount of supercritical fluid. The experiments were conducted in standard cold-seal pressure vessels at 680°C and 500 MPa in the T-P-XCO2 stability field of the calcite-forsterite assemblage for 2, 5, 10, 20, 40 and 80 days, respectively. The weight ratio of mineral to fluid in the starting mixture is 1.46; the fluid was a mixture of H2O and CO2 with the mole fraction of CO2 being 0.1. The results show that the oxygen isotope exchange between the minerals was accomplished via mineral-fluid exchange by a dual-mechanism, i.e. initial rapid exchange due to Ostwald ripening of both calcite and forsterite, followed by a slower diffusion-controlled process. Furthermore, for the given fluid composition, calcite shows a greater rate of dissolution-recrystallization and oxygen isotope exchange with fluid than forsterite. As a result, oxygen isotope fractionations between calcite and forsterite and between the minerals and the fluid can simply pass the equilibrium fractionations with time and even lead to crossover behavior. Once diffusion becomes a primary mechanism for further isotope exchange in the three-phase system, the rate of oxygen diffusion in calcite is equal to, or slightly less than that in forsterite.